METHODOLOGY FOR THE FORMATION OF CREATIVE ABILITIES OF STUDENTS IN THE TEACHING OF DERMATOVENEROLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides information that the development of medical education is organized on the basis of world standards for the reform of Medicine, and the establishment of quality education in medical education is of particular importance, at the beginning of the new century, many positive changes in medical education were made in many countries of the world, including Uzbekistan, aimed at improving the quality.